Global Progress on Molten Salt Reactors A Companion to Dolan's Molten Salt Reactors and Thorium Energy - Dolan, Thomas James; Dolan, Thomas James; Kutsch, John (Woodhead Publishing, 2024)
Global Progress on Molten Salt Reactors: A Companion to Dolan's Molten Salt Reactors and Thorium Energy, Second Edition presents global perspectives on the latest research and technological advances. Each case study utilizes a comprehensive template that guides the reader through country specific research. Useful data which can be applied to work and research is included, along with a list of references for further research. Researchers, professional engineers and policymakers will gain a broad picture of worldwide MSR activity and a deep understanding of how theory and practical guidance is applied in a variety of settings, including budgets, approaches and constraints. - Provides a collection of case studies from 23 countries, presenting their latest research and activities on Molten Salt Reactors - Based on chapter 26 of the first edition of Dolan's Molten Salt Reactors and Thorium Energy, this companion title presents expanded and more complete coverage of global activities and research - Includes advanced technologies, reactor designs and safety and management strategies